Foucault now : current perspectives in Foucault studies - Faubion, James D., 1957- (Cambridge, UK. : Polity Press, 2014)
This interdisciplinary volume brings together a group of esteemed scholars, recognized for their command of and insights into Foucault's oeuvre. They demonstrate the many respects in which Foucault's project of an ontology of the present remains vital and continues to yield compelling insights and show that an ontology of the present is restricted to no particular terrain, but instead ranges widely and on paths that frequently intersect.
Includes bibliographical references : (pages 243-263) and index.
Keywords: Foucault, Michel, -- 1926-1984 -- Criticism and interpretation; Social sciences -- Philosophy